Effectiveness of flyer stimulation to mother skills in stimulating toddler development - Fuadah Ashri Nurfurqoni; Sinta Nuryati; Dedes Fitria (Poltekkes Kemenkes Yogyakarta, 2019)
The development of a toddler is influencing by giving stimulate. According to Ministry of Health Republic of Indonesia in 2013, 16% toddler in Indonesia run into developmental disorder. Mother’s active role is very influencing children development. Its needed effort to increase mother ability who have a toddler so they can fulfill balance stimulate according to the toddler stage. The purpose of this study was to determine the effectiveness of the use of flyer stimulation for mother skills in stimulating toodler development. This study was using a queasy experiment method with pre and post-test with a controlling group. The subject was a mother who has the toddler in the working area of Gang Kelor Primary Health Center Bogor. The intervention that was given by using development stimulatory flyer for intervention group, and using Mother and Child Health (MCH) book for control group. The sample was 30 respondents for each group which fulfill inclusion criteria. This study starts from June to Oktober 2017. Variable was measured by observation list. Data was analyzed by the Wilcoxon test. The result shows that there was significant difference in the mother’s knowledge in the pre-test and post-test for giving stimulating using flyer (Mean difference= 27.70) and stimulating using MCH book (Mean difference= 7.47). Flyer development stimulation was more effective to increase a mother’s skill to stimulate toddler development at age 1-3 years than using MCH book (p-value <0.005) The flyers was effective in improving mother skills in stimulating toodler.